Oxylipins and Reactive Carbonyls as Regulators of the Plant Redox and Reactive Oxygen Species Network under Stress - Madita Knieper; Andrea Viehhauser; Karl-Josef Dietz (MDPI AG, 2023)
Reactive oxygen species (ROS), and in particular H2O2, serve as essential second messengers at low concentrations. However, excessive ROS accumulation leads to severe and irreversible cell damage. Hence, control of ROS levels is needed, especially under non-optimal growth conditions caused by abiotic or biotic stresses, which at least initially stimulate ROS synthesis. A complex network of thiol-sensitive proteins is instrumental in realizing tight ROS control; this is called the redox regulatory network. It consists of sensors, input elements, transmitters, and targets. Recent evidence revealed that the interplay of the redox network and oxylipins-molecules derived from oxygenation of polyunsaturated fatty acids, especially under high ROS levels-plays a decisive role in coupling ROS generation and subsequent stress defense signaling pathways in plants. This review aims to provide a broad overview of the current knowledge on the interaction of distinct oxylipins generated enzymatically (12-OPDA, 4-HNE, phytoprostanes) or non-enzymatically (MDA, acrolein) and components of the redox network. Further, recent findings on the contribution of oxylipins to environmental acclimatization will be discussed using flooding, herbivory, and establishment of thermotolerance as prime examples of relevant biotic and abiotic stresses.